(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Konoval O. A., Turkot T. I. New theoretical and methodological approaches to the organization of students’ independent work in the process of studying the special theory of relativity. The authors of the article offer the renovation of students’ self-study on the bases of binary, alternative, synergy, integration, individual and differentiating approaches, the development of pedagogic reflection, providing optimal integration with informational and educational environment of higher education institutes. The work highlights the logics and peculiarities of organizing self-study of future physics teachers in learning special relativity theory.